Professional Ethics and Social Service in a communally connected profession: A Socio-Aid Prospective - Shah Md Omer Faruqe Jubaer; Sadia Khan Swarna; Lipa Hoque Chowdhury; Syed Hasan Shahriar Rofi; Anas Siddique (Zien Journals, 2022)
Internal congruency and harmony between our beliefs and deeds, between the value we place on wanting to do our best for our customers and our genuine readiness to bring the best awareness and talents to that work, is what ethical behavior is all about. The first step in self-reflection should be to consider why we choose the professional role we have. We may return to that fundamental reason when we are perplexed by the centrifugal forces and chaos of situations, characters, and the myriad details on the periphery once we understand it. The reason we're in a role isn't always important to our life's purpose. It's what we believe we're here to do, what we believe our talents are. Sometimes the reason is only transitory, which is also useful to know. In that scenario, it's a good idea to go back and find the main aim to which this temporary goal ties. The main goal of this research paper is to define medical ethics and analyze the related legal framework in order to arrive at a solution from a medical standpoint. Because a relational ethic must take into account the web of relationships that goes beyond immediate human relationships to people of other races and nations, as well as all living creatures.
Keywords: Ethics; Professional ethics; Medical Ethics; Ideologies